Effectiveness of Acupuncture Therapy ST36 Zusanli ST40 Fenglong GV2O Baihui with a Combination of Cupping GV14 Dazhui in Patients with Hypertension in Simpang Luas Village, Sungai Are District, Ogan Komering Regency, South Ulu - Lestari, Okda; Purwanto; Sumanto; Mutiah, Nurmila (Indonesian Journal of Acupuncture, 2025)
Hypertension is one of the most significant health problems in the world. This condition is characterized by increased systolic and diastolic blood pressure that can lead to serious complications such as heart disease, stroke, and kidney failure. Treatment of hypertension generally uses anti-hypertensive drugs, but long-term use may cause side effects. This research is a quantitative research with a Quasi-Experimental design. The research subjects amounted to 40 people who were divided into two groups. Group I acupuncture therapy and group II acupuncture and cupping therapy. The results of data analysis using the Mann-Whitney test obtained a p-value of 0.004. This shows that the p<0.05 value means that cupping combination acupuncture therapy is effective in lowering blood pressure in hypertensive patients in Simpang Luas Village, Sungai Are District, Ogan Komerig Regency, South Ulu.